Legal basis for ensuring public security and order at the regional level and the place of administrative and legal norms among them (Bulletin of Kharkiv National University of Internal Affairs, 2022)
It has been noted that ensuring public security and order is the State's prerogative and involves an inevitable clash of public and private interests. At the same time, the specifics of the region and the variety of relations that arise within it are based on the norms of many branches of law, the key place among which belongs to administrative law. The legal framework for ensuring public security and order at the regional level has been proposed to be considered as a legal acts systemic set of different legal nature, the norms of which are aimed at regulating public relations in the relevant area.It has been stated that administrative law norms are key to the system of legal framework for ensuring public security and order, and this is confirmed by the following: firstly, the provisions of most legal acts are aimed at regulating the activities of public authorities and defining their administrative and legal status, including powers, functions, goals and objectives, etc; secondly, the legal framework for ensuring public security and order forms the strategic directions of the state policy on creating a secure environment in each individual region; in addition, such legal frameworks regulate the relationship between public authorities and society and local governments, defining the most effective models of cooperation to maintain security and order within the respective territory.